2000
DOI: 10.1515/ling.2000.021
|View full text |Cite
|
Sign up to set email alerts
|

Four types of morpheme: evidence from aphasia, code switching, and second-language acquisition

Abstract: This paper presents empirical evidence supporting a new model of morpheme classification called the 4-M model. This model emphasizes the notion that lemmas underlying different types of morphemes become salient at different levels of production. This explains their different distributions. While the 4-M model classifies morphemes, it is primarily a model of how morphemes are accessed. The argument is that particular instantiations of morphemes are classified as a consequence of the mechanisms that activate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(80 citation statements)
references
References 24 publications
1
78
0
1
Order By: Relevance
“…The unit of analysis in the present study was based on the complementiser phrase (hereafter CP). According to the 4M model (Myers-Scotton & Jake, 2000), CP, the projection of the complement node is the unit of analysis for bilingual speech. In the current study, eight hours of spontaneous conversations were transcribed and were categorised in different tables.…”
Section: Methodsmentioning
confidence: 99%
“…The unit of analysis in the present study was based on the complementiser phrase (hereafter CP). According to the 4M model (Myers-Scotton & Jake, 2000), CP, the projection of the complement node is the unit of analysis for bilingual speech. In the current study, eight hours of spontaneous conversations were transcribed and were categorised in different tables.…”
Section: Methodsmentioning
confidence: 99%
“…Grosjean, 1997) and preverbal message (cf. Myers- Scotton & Jake, 1995, 2000a to be desired. If the speaker chooses the monolingual mode, no CS will occur; if the speaker chooses the bilingual mode, then he/she must decide whether intersentential or intrasentential CS should be performed.…”
Section: The Bilingual Lemma Activation Modelmentioning
confidence: 99%
“…Myers-Scotton (2000) mentioned that when bilingual compound verbs appear, the 'do construction' is the only way to use the bare infinitive of the EL verb in the ML structure. In a study about CS between Dutch-Turkish bilingual speakers, Backus (1996) showed that the Dutch infinitive verbs and the Turkish auxiliary yap appear together to make a bilingual compound verb.…”
Section: Related Studies Involving Different Language Pairsmentioning
confidence: 99%